Ecological food sense : connections between food waste flows and food production in Enkanini Informal Settlement, Stellenbosch - Mollatt, Michelle Claire (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2014